Identifying sustainable rice cultivation zones in India: the implications of the crop water footprint - Prem Chand; Sulakshana Rao; Rajni Jain; Suresh Pal (Agricultural Economics Research Review, 2023)
This paper examines the water footprint of rice in the agroclimatic zones (ACZ) in India and identifies the sustainable rice-growing zones. The major rice-producing ACZs of the irrigated northwestern and semi-arid tropics are unsustainable. Rice can be cultivated sustainably in eastern, central, and (the coastal zones of) western India, because the water footprint is lower, and it can be lowered even more because the crop yield is very low. The study suggests that, based on the water availability and footprint, the cropping pattern in the ACZs needs to be realigned.